Advancements in green chemistry: sustainable synthesis and processes - Samuel, Humphrey Sam; Etim, Emmanuel Edet; Nweke-Maraizu, Ugo; Yakubu, Shedrach (Journal of the Belarusian State University. Chemistry, 2024)
An emerging area of chemistry called «green chemistry» is revolutionising how environmental and sustainability issues related to chemical synthesis and processes are handled. A key tactic for improving sustainability in the chemical sector is green chemistry. Recent developments in green chemistry have concentrated on environmentally friendly synthesis and processes, such as the effective and clean transformation of renewable raw materials, the development of novel reactions and techniques, the use of eco-friendly solvents and alternative energy sources, process intensification, and cutting-edge environmental technologies. These developments are promoting sustainability in the chemical sector and lowering the environmental effect of chemical operations.